Implementasi Pengendalian Pembangunan Hotel di Kabupaten Semarang (Peraturan Bupati No. 53 Tahun 2011) - Purba, Rido Maris; Rostyaningsih, Dewi; Marom, Aufarol (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Control is one aspect in the development of a State which has the role and influence are very important because it involves the lives of many people. In the process of development control, closely related to the Spatial as stated Act 26 of 2007. Its aims to provide harmony, harmony, balance, sustainability, and environmental success. The purpose of this study is to investigate the implementation process and analysis Regents Regulation No.53 of 2011 Regional Bandungan, Semarang discussing development control in Semarang District and the factors that influence a Regents Regulation impelementation No.53 of 2011This type of research used in this study is descriptive in order to give an idea or an explanation of the data acquisition and qualitative research prosedure, the data obtained from interviews, observations, and archival. The result of the study are considered relevant to the problem under study analyzed qualitatively through data reduction corresponding to the key problem in the study and focus on the main issues to be answered in this study The results showed that the implementation Regents Regulation No.53 of 2011 District Bandungan, Semarang city administrations has done sought to control hotel development in District Bandungan. But its constrainedbyseveralfactors, including (1) ZoningRegulations, there arebuildings thatstoodonthe borderroads, buildings, andriver banks; (2) Licensing, indifferencehotel ownerswhodo notcomply with theorderpermittingthe construction ofthe hotel; (3) disincentive and incentives, such as sanctionsandrespect for hotel owners who violate and abide by the rules, (4) communication, poor communication between the government and the owners of the hotel and (5) the disposition, less commitment on the part of implementing the policy. In overcoming these obstacles, there are some suggestions that can be done such as the need for socialization and commitment regarding the meaning and content of the established policies and regulations governing the four factors contained in policy implementation with regard to development control.